Hypoxia and Human Diseases - Zheng, Jing; Zhou, Chi (IntechOpen, 2017)
This book contains a total of 21 chapters, each of which was written by experts in the corresponding field. The objective of this book is to provide a comprehensive and updated overview of cellular and molecular mechanisms underlying hypoxia's impacts on human health, as well as current advances and future directions in the detection, recognition, and management of hypoxia-related disorders. This collection of articles provides a clear update in the area of hypoxia research for biomedical researchers, medical students, nurse practitioners, and practicing clinicians in the fields of high altitude biology, cardiovascular biology and medicine, tumor oncology, obstetrics, pediatrics, and orthodontics and for others who may be interested in hypoxia.